Innovation as an Agrotourism Competitive Excellence Strategy in Increasing Civet Coffee Product's Marketing Performance in Gianyar - Pande Ketut Ribek; I Gede Rihayana (Journal of International Conference Proceedings (JICP), 2019)
To increase sales of Luwak coffee agrotourism, the innovation strategy is in increasing the value of its sales. Through research entitled "Innovation as a Competitive Strategy for Competitiveness of Agro Tourism in Increasing Marketing Performance of Luwak Coffee Products in Gianyar. The purpose of this study is to find out the variables that are strengths, weaknesses, opportunities and threats faced by Luwak coffee agro tourism in marketing their products. Data collection techniques are carried out using interview, observation, and documentation methods. While analysis techniques are combined with SWOT analysis. From the results of the study, it is known that Luwak coffee agro-tourism has strength, namely: technical innovation in producing products with quality choices, design changes according to customer desires, developing ideas and changes in distribution systems. Besides the complete facilities, special prices, services, strategic location, employee appearance, mastery of foreign languages, and guides. While the weaknesses (Weakness) lack of maximum promotion, and lack of mastery of technology in the production of goods. Opportunities from the external environment are indicated by conducive indicators of Bali security stability, flexible local government policies, inflation rates and the rupiah exchange rate against the US dollar. While the threat (Treats) the growth rate of agrotourism and the development of technology is getting faster. Marketing performance that is done is to improve product quality, vigorous promotions, price adjustments, best services and improve cooperative relations with various companies.